Nurses' Participation in Limited Resuscitation: Gray Areas in End of Life Decision-Making. Issue 4 (2nd October 2021) - Stokes, Felicia; Zoucha, Rick
Abstract: Historically nurses have lacked significant input in end-of-life decision-making, despite being an integral part of care. Nurses experience negative feelings and moral conflict when forced to aggressively deliver care to patients at the EOL. As a result, nurses participate in slow codes, described as a limited resuscitation effort with no intended benefit of patient survival. The purpose of this study was to explore and understand the process nurses followed when making decisions about participation in limited resuscitation. Five core categories emerged that describe this theory: (1) recognition of patient and family values at the EOL; (2) stretching time and reluctance in decision-making; (3) harm and suffering caused by the physical components of CPR; (4) nurse's emotional and moral response to delivering aggressive care, and; (5) choosing limited resuscitation with or without a physician order. Several factors in end-of-life disputes contribute to negative feelings and moral distress driving some nurses to perform slow codes in order to preserve their own moral conflict, while other nurses refrain unless specifically ordered by physicians to provide limited care through tailored orders.